Layanan Bimbingan Klasikal Bidang Belajar untuk Meningkatkan Motivasi Berprestasi pada Siswa Underachiever Gifted - Rismayadi, Hendri; Suherman, Suherman; Yusuf, Syamsu (Universitas Ahmad Dahlan, 2017)
This study aimed to understand the effectiveness of the classroom guidance activity for the academic aspect to improve achievement motivation underachiever gifted students in SMA Negeri 4 Bandung. This was an experimental study with pre-experimental design. Â The data were collected through achievement motivation scale. The subject of this study was 30 students of class X SMA Negeri 4 Bandung. The sample was taken by using purposive sampling technique. The data analysis technique of this study was paired sample t-test statistical formula.Â The result of this study showed that classroom guidance activity for the academic aspect was effective to improve achievement motivation underachiever gifted students. This study generates a new strategy in the form of classroom guidance activity for the academic aspect was effective to improve achievement motivation underachiever gifted students.